Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Organization Citizenship Behavior (OCB) (Studi Pada Guru MA Al-Ijtihad Desa Danger Kecamatan Masbagik) - Luthfi Kandias; Thatok Asmony; Siti Nurmayani; Irhas Irhas (Universitas Hamzanwadi, 2023)
This study is the effect of emotional intelligence and spiritual intelligence on organization citizenship behavior (OCB) at MA Al-Ijtihad Danger. This study used causal associative research with a quantitative approach. To collect the data the researcher used census, it was a sampling technique that all members of the population was used as samples. However, the techniques of data collection were questionnaires, interviews and documentation. The analisysis tool was performed using multiple liner regression analysis using the SPSS 16.0 program. The results of this study was the influence of emotional intelligence and spiritual intelligence on organizational citizenship behavior (OCB) at the MA AL-IJTIHAD teacher, DANGER VILLAGE, MASBAGIK was found that emotional intelligence had a positive and significant effect on organizational citizenship behavior (OCB). It means that if the emotional intelligence is high, the higher Organizational Citizenship Behavior (OCB) will be. On the other hand, if the Emotional Intelligence is low, the lower Organizational Citizenship Behavior (OCB) will be. Likewise, spiritual intelligence had a positive and significant effect on Organizational Citizenship Behavior (OCB). It means that if the Spiritual Intelligence is high, the Organizational Citizenship Behavior (OCB) will be higher. Conversely, if Spiritual Intelligence is low, the Organizational Citizenship Behavior (OCB) will be lower